2021
DOI: 10.3390/min11090956
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Relative Permeability Characteristics for CO2 in Sandstone under High Temperature and Overburden Pressure

Abstract: In this study, CO2 seepage of sandstone samples from the Taiyuan-Shanxi Formation coal seam roof in Ordos Basin, China, under temperature-stress coupling was studied with the aid of the TAWD-2000 coal rock mechanics-seepage test system. Furthermore, the evolution law and influencing factors on permeability for CO2 in sandstone samples with temperature and axial pressure were systematically analyzed. The results disclose that the permeability of sandstone decreases with the increase in stress. The lower the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The sampling position of experimental rock samples is illustrated in Figure 1 [ 30 ], and they are processed into standard specimens, which are divided into six groups (18 sandstone samples in total) according to different experimental conditions. The specific parameters are shown in Table 1 [ 30 ] below.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sampling position of experimental rock samples is illustrated in Figure 1 [ 30 ], and they are processed into standard specimens, which are divided into six groups (18 sandstone samples in total) according to different experimental conditions. The specific parameters are shown in Table 1 [ 30 ] below.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…First, the samples were put into the atmosphere oven with the mouth sealed, and then the oven door was closed. Next, the heating rates were set to 10 °C/min and the heating temperatures were set according to Table 1 [ 30 ], with three samples in each temperature gradient. The heating treatment under each temperature gradient lasted for 2 h. After being heated, the samples were not taken out immediately until the oven had naturally cooled down to about 50 °C ( Figure 2 [ 30 ]).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, from the view of cavity expansion, Luo and Wang [8], Akbarzadeh and Chalaturnyk [9], Janoszek et al [10] investigated the confining rock during coal combustion, suggesting obvious changes in the mechanical properties of rock at high temperature and pore pressure. The permeability of near-field rock of a UCG cavity, as announced by Otto and Kempka [11], Wałowski [12], Madiutomo et al [13], Ding et al [14], experiences significant change during cavity expansion, while that of far-field rock is influenced to a limited degree. Meng et al [5], Duan et al [15], Jin et al [16] investigated the fracture characteristics, evolution law and influence tendency induced by pore pressure, thermal damage, etc.…”
Section: Introductionmentioning
confidence: 93%
“…The study showed that the increase in temperature could significantly degrade the physical properties of rock, and the increase in confining pressure could improve the strength and deformation of rock. Ding et al [36] conducted a CO 2 seepage test on sandstone under the action of thermodynamic coupling, and the study showed that the permeability of sandstone decreased with the rise in stress, and first decreased and then increased with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%